Determination of Deposits through Exchange Rates: Analysis of Interest Rates, Trust in Banks, and Public Income - Christophorus Indra Wahyu Putra; Hasanuddin Hasanuddin; Rosalina Siagian (Siber Nusantara of Economic and Finance Review, 2026)
This study aims to analyze the influence of interest rates, trust in banks, and public income on deposits through the exchange rate as a mediating variable in the banking sector in Indonesia. The approach used was a descriptive qualitative approach using the Systematic Literature Review (SLR) method on 40 nationally and internationally reputable scientific articles. Data were analyzed through the stages of reduction, presentation, and synthesis to produce a comprehensive conceptual model. The results indicate that: 1) Interest rates affect the exchange rate; 2) Trust in banks affects the exchange rate; 3) Public income affects the exchange rate; 4) Interest rates affect deposits; 5) Trust in banks affects deposits; 6) Public income affects deposits; 7) The exchange rate affects deposits; 8) Interest rates affect deposits through the exchange rate; 9) Trust in banks affects deposits through the exchange rate; 10) Public income affects deposits through the exchange rate.